Fire‐mediated habitat change regulates woodland bird species and functional group occurrence. Issue 8 (27th September 2019) - Gosper, Carl R.; Watson, Simon J.; Fox, Elizabeth; Burbidge, Allan H.; Craig, Michael D.; Douglas, Tegan K.; Fitzsimons, James A.; McNee, Shapelle; Nicholls, A. O.; O'Connor, James; Prober, Suzanne M.; Watson, David M.; et al.
Abstract: In an era characterized by recurrent large wildfires in many parts of the globe, there is a critical need to understand how animal species respond to fires, the rates at which populations can recover, and the functional changes fires may cause. Using quantified changes in habitat parameters over a ~400‐yr post‐fire chronosequence in an obligate‐seeding Australian eucalypt woodland, we build and test predictions of how birds, as individual species and aggregated into functional groups according to their use of specific habitat resources, respond to time since fire. Individual bird species exhibited four generalized response types to time since fire: incline, decline, delayed, and bell. All significant relationships between bird functional group richness or abundance and time since fire were consistent with predictions based on known time‐since‐fire‐associated changes in habitat features putatively important for these bird groups. Consequently, we argue that the bird community is responding to post‐fire successional changes in habitat as per the habitat accommodation model, rather than to time since fire per se, and that our functional framework will be of value in predicting bird responses to future disturbances in this and other obligate‐seeder forest and woodland ecosystems. Most bird species and functional groups that were affected by time since fire were associated with long‐unburned woodlands. In the context of recent large, stand‐replacement wildfires that have affected a substantial proportion of obligate‐seeder eucalypt woodlands, and the multi‐century timescales over which post‐fire succession occurs, it would appear preferable from a bird conservation perspective if fires initiating loss of currently long‐unburned woodlands were minimized. Once long‐unburned woodlands are transformed by fire into recently burned woodlands, there is limited scope for alternative management interventions to accelerate the rate of habitat development after fire, or supplement the resources formerly provided to birds by long‐unburned woodlands, with the limited exception of augmenting hollow availability for key hollow‐nesting species.